The Liberalization Aspect Of Trademark Law Of Indonesia In The Asean Free Trading - Delfiyanti, Delfiyanti (Nagari Law Review, 2024)
Intellectual property rights are rights that are protected by law and one of them is related to brands. The use of brands in trade both nationally and internationally has increased from year to year. Along with global trade liberalization, brand use continues to increase. In regional trade, it is known as liberalization in ASEAN. There are various agreements made by ASEAN member countries to improve the welfare of the ASEAN Community as contained in the 2008 ASEAN Charter. Meanwhile, for brand protection, an ASEAN Intellectual Property Rights Action Plan agreement was created. This agreement contains ASEAN's action plan to protect brands and use of brands without permission. For Indonesia, this is an agreement that is harmonized with Law no. 20 concerning Marks and Geographical Indications.